2017
DOI: 10.4103/0022-3859.194209
|View full text |Cite
|
Sign up to set email alerts
|

Postradiotherapy small cell neuroendocrine carcinoma of base of tongue

Abstract: Small cell neuroendocrine carcinoma (NEC) of the tongue is an extremely rare entity with only seven cases reported in literature till date. These are high-grade tumors with a dismal prognosis. There is much ambiguity regarding the classification, treatment protocols and prognostic factors of these tumors due to the paucity of studies. We describe an exceptionally rare and unusual case of small cell NEC of the base of tongue arising in an elderly man 6 years after receiving radiotherapy for the treatment of squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A PRISMA diagram outlining the literature search is shown in Figure 1. Fifty full‐text articles published from 1987 to 2020 were ultimately included in this systematic review 4,5,8–12,18–60 . Further details regarding these publications including the Oxford level of evidence can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A PRISMA diagram outlining the literature search is shown in Figure 1. Fifty full‐text articles published from 1987 to 2020 were ultimately included in this systematic review 4,5,8–12,18–60 . Further details regarding these publications including the Oxford level of evidence can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…NEC can occur in various organs of the body, of which the lung is the most common organ, while NEC occurring in the oral mucosa is very rare, such as the tongue [10] . Published case reports have suggested that NEC of the tongue mostly occurs in middle-aged and elderly patients (range 40-79 years), is more common in males and is relatively uncommon in females [2] , [3] , [4] , [5] , [6] , [7] , [8] . A case report mentioned the 18 F-FDG PET/CT findings of tongue NEC but did not detail the uptake of FDG in the lesions [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine carcinoma (NEC) can occur in any epithelial organ, including the lung, digestive system, breast, urogenital system, and head and neck. The larynx is the most common site of NEC in the head and neck, and it can also occur in the nasal cavity, nasopharynx, middle ear and salivary glands [1] , while it is very rare in the tongue and has only been reported in several case reports [2] , [3] , [4] , [5] , [6] , [7] , [8] . Few studies have sufficiently discussed the imaging performance of tongue NEC.…”
Section: Introductionmentioning
confidence: 99%
“…CK7 is distributed in many glandular and ductal tissues such as respiratory epithelium, breast epithelium, biliary tract epithelium, urothelium, mesothelium, and apocrine glands 16,18–22. As a common tumor marker for adenocarcinoma,16,17 CK7 has also frequently been detected in neuroendocrine-derived tumors, including pulmonary neuroendocrine tumors,15 gastrointestinal neuroendocrine neoplasms,16,23 neuroendocrine carcinomas (NECs) of the uterine cervix,24 and primary cutaneous squamous cell carcinoma,25 as well as head and neck26 and oral tumors 27. However, the diagnostic specificity and sensitivity of CK7, especially its staining pattern and intensity, have not been evaluated in NEC.…”
mentioning
confidence: 99%
“…16,[18][19][20][21][22] As a common tumor marker for adenocarcinoma, 16,17 CK7 has also frequently been detected in neuroendocrine-derived tumors, including pulmonary neuroendocrine tumors, 15 gastrointestinal neuroendocrine neoplasms, 16,23 neuroendocrine carcinomas (NECs) of the uterine cervix, 24 and primary cutaneous squamous cell carcinoma, 25 as well as head and neck 26 and oral tumors. 27 However, the diagnostic specificity and sensitivity of CK7, especially its staining pattern and intensity, have not been evaluated in NEC. Thus, in our study, we investigated the immunohistochemical expression of CK7 in SmCC versus LCNEC of urinary bladder and lung.…”
mentioning
confidence: 99%